Warning System and Monitoring Sulfur Dioxide (SO2) Via SMS Gateway Based on Microcontroller Using Sensor MQ-136 at Mount Tangkuban Parahu - Tri Rahajoeningroem (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
In this research, the warning systems and monitoring of SO2 gas conditions designed using sms gateway technology with assistance MQ136 sensor gas to detect the presence of SO2 gas and ATmega16 microcontroller as the processor. The SO2 gas concentration value will indicate a condition with a normal, alert, or hazard warning, it can be determined and determined from the laboratory test results. SMS will be sent to five number of destination if the concentration exceeds the threshold value set. System monitoring is done by sending an sms to device which contained by command to transmit gas concentration values which detected via sms to the number of the sender. This device is also equipped with a gas alarm if condition is danger and will stop ringing if it is below the danger threshold.